PENERAPAN MODEL CORE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MATERI BALOK DI MTs. MIFTAHUL ULUM - Rizqiyatil Izza, Ita Ela; Irawati, Tri Novita; Al Ayubi, Sholahuddin (FKIP Universitas Islam Jember, 2022)
The goal of this study was improving student activities and learning outcomes through the CORE learning model in block material for class VIII MTs Miftahul Ulum in the 2019/2020 school year. The type of research that researchers used was classroom action research. Which was the subject in this research were 22 students of class VIII MTs Miftahul Ulum Banyuanyar. Cassical initial observations of student learning outcomes only reached 59%, in cycle I, the percentage of classical student learning activities was 77% in the fairly active category and learning outcomes reached 77%. In cycle II, the percentage of classical student learning activities was 85% in the fairly active category, and the learning outcomes achieved 90% completeness. Of these success indicators, it could be concluded that learning with CORE model of student learning activities and student learning outcomes has increased for class VIII students of MTs Miftahul Ulum. Keywords: CORE model, activities, learning outcomes